Management models from an Islamic perspective - Fontaine, Rodrigue Ancelot Harvey (IIUM Press, 2011)
This chapter explores the Islamic perspective on management models. A literature review identified three main streams in the MIP literature. These are the emphasis on paradigms, the emphasis on justice and the desire to extend conventional management theories. These three points are then applied to how managers use management models. Generally, Muslim managers use conventional management models and modify them to deal with Islamic concerns. At the same time, they use purely Islamic models to guide their thinking. Unfortunately, the number of potential management models is virtually unlimited. Based on the principle of the aims of the Islamic legal system and the principle of Evidence Based Management, not all management models are suitable for Muslim managers. Further research is needed to deal with the issue of the right method to be used in MIP and a detailed study of the usefulness of modified management models.